Regulation of human heme oxygenase in endothelial cells by using sense and antisense retroviral constructs - Quan, Shuo (The National Academy of Sciences, 2001)
Our objective was to determine whether overexpression and underexpression of human heme oxygenase (HHO)-1 could be controlled on a long-term basis by introduction of the HO-1 gene in sense (S) and antisense (AS) orientation with an appropriate vector into endothelial cells. Retroviral vector (LXSN) containing viral long terminal repeat promoter-driven human HO-1 S (LSN-HHO-1) and LXSN vectors containing HHO-1 promoter (HOP)-controlled HHO-1 S and AS (LSN-HOP-HHO-1 and LSN-HOP-HHO-1-AS) sequences were constructed and used to transfect rat lung microvessel endothelial cells (RLMV cells) and human dermal microvessel endothelial cells (HMEC-1 cells). RLMV cells transduced with HHO-1 S expressed human HO-1 mRNA and HO-1 protein associated with elevation in total HO activity compared with nontransduced cells. Vector-mediated expression of HHO-1 S or AS under control of HOP resulted in effective production of HO-1 or blocked induction of endogenous human HO-1 in HMEC-1 cells, respectively. Overexpression of HO-1 AS was associated with a long-term decrease (45%) of endogenous HO-1 protein and an increase (167%) in unmetabolized exogenous heme in HMEC-1 cells. Carbon monoxide (CO) production in HO-1 S- or AS-transduced HMEC-1 cells after heme treatment was increased (159%) or decreased (50%), respectively, compared with nontransduced cells. HO-2 protein levels did not change. These findings demonstrate that HHO-1 S and AS retroviral constructs are functional in enhancing and reducing HO activity, respectively, and thus can be used to regulate cellular heme levels, the activity of heme-dependent enzymes, and the rate of heme catabolism to CO and bilirubin.